O projeto de escritura literária de Ruffato : reflexões sobre a estética do romance brasileiro contemporâneo - Buscácio, Lívia Letícia Belmiro (2007)
Literary writing project of Luiz Ruffato: reflections about the esthetic of contemporary brazilian novel aim to investigate the characteristic of the texture of Luiz Ruffato s novel, considering the union of the linguistics aspects, literary and sociological for esthetic comprehension. The analysis is based in the reading of the novel s process of creation, 2001, eles eram muitos cavalos, as the two first novels Inferno Provisório Mamma, son tanto felice and O mundo inimigo, both from 2005 which are based in the rewrite of Histórias de remorsos e rancores ( 1998) and (os sobreviventes) (2000). The intention is to discuss the maturate of the narrator in the literary enunciation, considering the more effective presence of his self-criticism in the Romanesque texture, which is expressed due to the improvement on pluralinguism and the reflection about social context and de literary deeds itself, what constitutes the bases of Romanesque gender according to Bakhtin. Investigating the narrator s reference about his own enunciation, we notice the other gender s parody analyzed according to Bakhtin and Hutcheon, and the use of the forms of reported discourse, hipertaxe, typography marks and deixis, according to Authier Revuz. Such resources give voice to the narrator s enunciation of the characters, configuring what Authier Revuz names as heterogeneity showed, it means, explicit marks of the dialogism in the enunciation. The stylistics resources are attached to the rewrite proposal of the Brazilian History, once it gives voice to whom was excluded from the official History through the polyphony perceived through the characters experiences in the agricultural spaces, industrial and national post-modern. According to it, it s noticed that the rewrite of the Brazilian History is based in the perspective of the History of mentalities, in a way that it shows the Brazilian s society profile from the experiences lead by the ethic of agricultural spaces, industrial and post-modern. The historical reflection is also linked to Ruffato s masterpiece rewrite, as the two first volumes reorganize previous publications from the space category and a bigger intervention of the narrator, through the stylistics resources. In short, we verify that literature, above all the novel, requires an analysis based on transdisciplinary as an esthetic thought and about the literary esthetic.